KAPABILITAS PENGELOLA MENGEMBANGKAN UNIT USAHA BADAN USAHA MILIK DESA (BUMDES) PENGALIHAN KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR TAHUN 2020-2022 - Jusman '; Adlin ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The capability of the manager to develop the BRILink and Lundry business untis in the transfer village. as for the problems in this study, namely, BUMDes , managers are still weak, business units are the same as those owned by the community, business units income is not maximized, one of the main targets of the Rasau Kuning BUMDes organization is to improve the economy and increase profits. One way to encouage development at for the village government to be given authority by the government to independently manage the scope of the village through these institutions, one of which is village-owned enterprises (BUMDes). (Kushartono, 2016). BRILink is a busines units established by the Rasau Kuning village of the transfer which is supported by the village government in activities involving the transfer village economy. Laundry is a BUMDes business units of Rasau Kuning deda transfer which has been managed to date. This study uses a qualitative approach perspecitve. The purpose of thus research is to see the capabilites of manager of the BUMDes Rasau Kuning village business units in the transfer of the keritang sub-district, indragiri downstream disrich, in 2020-2022. this research uses capability theory, Hasan Basri, this type of researct is descriptive. The locations of this researct is in the village of diversion, indragiri downstream district. The results of the research and management capabilites in developing village-owned business units (BUMDes) for the transfer of keritang sub-district, indragiri regency downstream in 2020-2022, can be concluded as follws 1. The ability provided by BUMDes managers in developing business units is currently not optimal, whether it is income the income of the business units, this can be proven by the results of the research date on the BUMDes Rasau Kuning both in terms of capital, employees, turnover, figures and profit. Keyword : Work Ability, BUMDes Ability, Conceptual Ability, Leadership Ability